2010
DOI: 10.1002/wsbm.110
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways that control cell migration: models and analysis

Abstract: Dissecting the intracellular signaling mechanisms that govern the movement of eukaryotic cells presents a major challenge, not only because of the large number of molecular players involved, but even more so because of the dynamic nature of their regulation by both biochemical and mechanical interactions. Computational modeling and analysis have emerged as useful tools for understanding how the physical properties of cells and their microenvironment are coupled with certain biochemical pathways to actuate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 57 publications
1
49
0
Order By: Relevance
“…22 Invasion is initiated and maintained by specific signaling molecules, pathways that control cytoskeletal dynamics and changes in cell-cell adhesion and/or cell-extracellular matrix interaction, finally culminating in migration and extravasation/intravasation of cells into adjacent tissues. 23,24 This study indicates that MIEN1 is a critical molecular determinant in these processes, resulting in metastatic dissemination of tumor cells. Using RNA interference, we transiently suppressed MIEN1 expression in OSCC-derived OSC-2 cells that have high endogenous MIEN1 expression.…”
Section: Discussionmentioning
confidence: 74%
“…22 Invasion is initiated and maintained by specific signaling molecules, pathways that control cytoskeletal dynamics and changes in cell-cell adhesion and/or cell-extracellular matrix interaction, finally culminating in migration and extravasation/intravasation of cells into adjacent tissues. 23,24 This study indicates that MIEN1 is a critical molecular determinant in these processes, resulting in metastatic dissemination of tumor cells. Using RNA interference, we transiently suppressed MIEN1 expression in OSCC-derived OSC-2 cells that have high endogenous MIEN1 expression.…”
Section: Discussionmentioning
confidence: 74%
“…There was no significant difference in the actin structures of the H9 and PLEKHG3 −/− cells. The elongated cell shape in the PLEKHG3 −/− cells might result from the enrichment of myosin II at the trailing edge of cells, which leads to antagonistic protrusion activity (38,39), or from an asymmetric localization of the Arp2/3 complex to the leading edge of the elongated cell (36). Here, we observed that PA-Rac1 led to the formation of lamellipodia, and PLEKHG3 was detected in the newly formed protrusion area on a characteristic time scale of ∼30 s. Closer observation showed the recruitment of PLEKHG3 at the newly formed actin filaments at the leading edge.…”
Section: Discussionmentioning
confidence: 99%
“…oxygen levels and blood flow) result in whole population dynamics, and can be built upon to include complex cell-cell signaling networks. 57,58 The future of trophoblast migration studies may be to apply these tested techniques to build upon our knowledge of the mechanisms controlling trophoblast invasion and spiral artery remodeling. Indeed, our ability to capture data on trophoblast migration data that can be used in this way to understand normal and pathological placentation is of particular importance given the difficulties that studying the process in vivo entails.…”
Section: Future Directionsmentioning
confidence: 99%